Estudio de mercado para determinar el grado de aceptación de yogurt persa en la ciudad de Quevedo - Samaniego Montenegro, Marco Antonio (2013)
The carrying out of research work started due to the problem of the lack of knowledge on the degree of acceptance that has Yogurt Persian among consumers in the city of Quevedo, which is based on the lack of positioning strategies that allow recall the brands that are offered in the Promenade Shopping. Started as a first step the formulation of the problem of the same research that established as follows: to what extent the lack of a market study that allow for a better understanding of the acceptance of products of the Persian Yogurt company, influences knowledge of consumer behavior of the market of Quevedo?with the formulated problem raised by the objectives of the research that routed toward the solution of the same. The overall objective was to determine the degree of acceptance that has Yogurt Persian among consumers in the city of Quevedo. The information sources that were used to capture the data necessary to comply with the investigation were primary and secondary. In the primary a questionnaire was developed from questions that were applied to users of the Promenade Shopping that frequent commonly independent they are clients of the business or not.By the side of the secondary source documentary research was conducted on important issues such as: market research, sales, training of personnel, market, analysis of the target market, analysis of the BCG matrix, consumers, positioning strategies, among others. The data obtained through the investigation allowed to bring a potential solution to the problems that affect the company. The solution is routed toward the design of a new concept of positioning based on product differentiation, organizing strategies, and to improve the corporate image of Yogurt in the Persian city of Quevedo